Intimate Partner Violence and Its Effects on Maternal and Child Health: A Longitudinal Study in Bener Meriah Regency, Aceh, Indonesia - Widya Apriani; Irdayani; Hida Yana (Open Access Indonesia Journal of Social Sciences, 2024)
Intimate partner violence (IPV) is a significant public health issue with devastating consequences for maternal and child health. This study investigates the prevalence and impact of IPV on pregnant women and their children in Bener Meriah Regency, Aceh, Indonesia, a region with limited research on this topic. A longitudinal study was conducted with 250 pregnant women recruited from antenatal clinics in Bener Meriah Regency. Data were collected through questionnaires and interviews at three time points: during pregnancy, six months postpartum, and one year postpartum. The questionnaires assessed IPV experiences, maternal mental health (depression, anxiety, and stress), and child health outcomes (birth weight, growth, and development). The prevalence of IPV during pregnancy was 32%. Women who experienced IPV were significantly more likely to suffer from depression, anxiety, and stress during pregnancy and postpartum. IPV was also associated with lower birth weight and an increased risk of developmental delays in children. In conclusion, this study highlights the serious consequences of IPV for maternal and child health in Bener Meriah Regency. The findings underscore the urgent need for IPV screening and intervention programs in antenatal and postnatal care settings. Midwives play a critical role in identifying and supporting women experiencing IPV.